PENGARUH UKURAN PERUSAHAAN, STRUKTUR MODAL DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Sembiring, Sabeth; Shalini, Witya; Mahendra, A.; Parhusip, Poltak T. (UNIKA Santo Thomas, 2024)
This research aims to obtain empirical evidence of the influence of firm size, capital structure, and liquidity variables on the financial performance of Mining Companies listed on the IDX. This type of research is quantitative research. The data used in this research is secondary data. The population in this study includes all Mining Companies listed on the IDX in the 2020-2022 periods. The sample in this study was 18 companies that met the criteria. The sampling technique in this research used purposive sampling. The data analysis used to test the hypothesis is multiple linear regression with a significance level of 5% and using SPSS version 23 tools. The results of this study show that the Firm Size and Capital Structure variables have a significant and influential effect on Financial Performance partially, while the Liquidity variable has no partial effect on Financial Performance. Firm Size, Capital Structure, and Liquidity simultaneously influence Financial Performance